Civil Society Democracy in Indonesia Studies: A Systematic Literature Review (SLR) : Studi Demokrasi Masyarakat Sipil di Indonesia; Tinjauan Sistematic Literature Review - Shoffanisa Alifiani; Salahudin; Muhammad Firdaus (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2024)
This research aims to analyze the importance of the role of civil society in democracy, recognized as a prerequisite and indicator of democratization. The research method applied in this study is a sistematic literature review using 140 scientific articles sourced from the Scopus database. The article review utilizes the VOSviewer application. The results of this study reveal that democracy is a political sistem that refers to freedom, participation, and competition, with several supporting elements such as active participation of the public in societal, national, and state life; recognition of the rule of law and equality among citizens; civilian and military supremacy; freedom of expression, speech, assembly, organization, religion, belief, and self-determination. The study also shows that democracy is a broad and complex concept, with variations between liberal democracy and sosial democracy. This research contributes to the development of democratization in Indonesia by addressing efforts to reduce sosial inequality entrenched within Indonesia's democracy.